The Impact of Using Kahoot Application as an Interactive Learning Media in Improving the Digital Literacy Abilities of Elementary School Students - Aulia Putri Soenario; Yena Mardiani; Randi Randi; Wiwinda Wiwinda; Dini Widiyanti (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study aims to examine the impact of using the Kahoot application as an interactive learning medium in improving the digital literacy skills of elementary school students, particularly in the dimensions of critical thinking, digital collaboration, and digital ethics. The main problem behind this study is the passive participation of students and the lack of variety of digital learning media at SDN 76, Bengkulu City. The method used is a quantitative approach with a quasi-experimental design involving 39 third-grade students who were divided into an experimental group and a control group. The sampling technique was carried out using purposive sampling, while data collection used test instruments (pre-test and post-test), observation, and documentation. The results showed that the use of Kahoot significantly improved students' digital literacy, where the average score increased drastically from 30% in the initial stage to 75% after the intervention. Statistical analysis through a t-test showed a significance value of 0.000 (<0.05), which proved a very significant difference in ability due to the use of interactive media. The research instrument was also proven to be very reliable with a Cronbach's Alpha value of 0.974. In conclusion, Kahoot is effective not only in increasing active engagement and motivation to learn through gamification elements, but also as a powerful tool for developing basic operational skills, information navigation, and digital ethics awareness in elementary school students.